Clinical Improvement of Erythrodermic Psoriasis Patient Treated with Methotrexate: A Case Report - Cagar Irwin Taufan Pamungkas; Asri Ayu Firdausi; Agnellia Maulidya Utami; Elfindri Okgandita Veranie; Anselma Dyah Kartika Hadi (Faculty of Medicine, University of Jember, 2023)
Erythrodermic psoriasis (EP) is a rare form of psoriasis but has a high mortality and morbidity rate. The management of erythrodermic psoriasis includes prevention of complications and administration of immunosuppressant drugs such as methotrexate. This article reports the case of a 37-year-old man with complaints of red, scaly spots almost all over his body since the past month. Initially, the red spots only appeared on the right and left arms and legs. On dermatological examination found lesions on >90% of the patient's total body area in the form of erythematous patches, well-defined, irregular shape and covered with thick scales, there was onycholysis of the toenails, and the Karvslek phenomenon in the patient. Based on the history and physical examination, the patient was diagnosed with erythrodermic psoriasis with a PASI score of 60.2. The patient received oral methotrexate therapy 7.5 mg/week, folic acid once daily, cetirizine 10 mg twice daily, and topical therapy with desoximetasone cream 0.25%. Methotrexate is taken alternately with a single dose of 2.5 mg. Evaluation of patients at 1 month after therapy showed improvement in clinical symptoms with reduced subjective symptoms followed by a change in the PASI score to 45.8. Proper diagnosis and management as well as monitoring for side effects of medication can reduce morbidity and prevent complications from EP. Keywords: Erythrodermic psoriasis, treatment, methothrexate.